Pengenalan Dasar Kecerdasan Buatan Pada Siswa SMK Negeri 5 Dan SMK Negeri 7 Manado : Introduction to Basic Artificial Intelligence for Students of SMK Negeri 5 Dan SMK Negeri 7 Manado (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
AbstractThe importance of knowledge about Artificial Intelligence in the Industrial Revolution 5.0 Era forces young people, even at school age, to be able to learn related to Artificial Intelligence. For the sake of advancing the insight of the upper secondary level, for the first time in SMK Negeri 5 and SMK Negeri 7 Manado basic training was carried out on Artificial Intelligence. The survey of prospective training participants at this school showed that 67.9% had heard of Artificial Intelligence, but 56.25% did not understand what Artificial Intelligence meant, and 98.71% had never made an application using Artificial Intelligence. This non-coding training was conducted in small groups of 3-5 people per 1 computer and one assistant. The survey results after the training showed that 78% had no difficulty during the training, their understanding of Artificial Intelligence increased to 69.5%, and 58,75% of students could create Artificial Intelligence programs.